Impact of Technical Barriers to Trade on Argentine Exports and Labor Markets - Gabriel Sánchez; María Laura Alzúa; Inés Butler (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2008)
While tariff and quota barriers in agricultural, food and manufactured products have been declining due to the proliferation of multilateral trade agreements, there is increasing debate regarding the impact of product and process standards and technical regulations, since they may have become a subtler form of protection. One of the possible effects of increasing standards in developing countries is that it may affect the size of the exporting sector, with adverse effects on labor markets. We test such effect for the case of Argentina using firm level data for the manufacturing sector. We find evidence of a reduction in export shares due to an increase in standard stringency. Moreover, there is an increase in the skill ratio for exporting firms. The overall effect of standard stringency on average wages of exporting firms is negative, supporting the idea that lower net producer prices, due to a higher cost of standard compliance, are passed on to workers.
Keywords: 330; Export; Nichttarifäre Handelshemmnisse; Beschäftigungseffekt; Lohnstruktur; Argentinien